(untitled) (Вісник Кримінологічної асоціації України, 2024)
In many cases, the existing legal regulations are not adequate to solve the legal problems created by the Internet. Solving the legal problems created by the Internet with existing positive regulations is a situation specific to the special field of law. In cases where the existing normative documents are insufficient, it is considered appropriate to add new provisions that complement each other, and if this is not possible, to make independent legal regulations. The fact that such arrangements are based on doctrine rather than spontaneity can ultimately lead to successful practice. Therefore, the interpretation of the human rights aspect of issues related to virtual space is one of the most important topics today. The most important issue related to the protection of human rights violated in the virtual space is the resolution of the issue of jurisdiction. Issues related to the Internet have also been reflected in all international declarations adopted in the field of information society construction, including the provision of information rights. At the regional level, the Declaration "On Freedom of Communication on the Internet" adopted by the Committee of Ministers of the Council of Europe in 2003, the Recommendations of the Committee of Ministers of the Council of Europe on the Human Rights Guide for Internet Users to Member States, etc. such documents are of special importance for the regulation of Internet legal relations. However, no international norm fully covers the issue of jurisdiction in virtual space. In the presented article, as a result of the research, it was concluded that it is necessary to create unified substantive and procedural legal norms that are mandatory for all in order to solve jurisdictional problems in the virtual space. Acceleration of integration and globalization processes in the world increases the interest of states in the unification of their legal norms. Because the countries of the world, which often protect their citizens from violations of their rights on the Internet, as well as from more dangerous information wars and psychological attacks, need the existence of a unified legal regulation. For this purpose, the creation and unification of legal norms that resolve jurisdictional issues in the virtual space should be implemented at different levels: bilateral, regional and universal levels